The influence of social media marketing on Generation Z’s buying behavior of livestock products - AISYAH NUR MAHARANI BURHANUDDIN; HASTANG HASTANG; ABDUL RAZAK MUNIR (Smujo International, 2025)
Abstract. Burhanuddin ANM, Hastang, Munir AR. 2025. The influence of social media marketing on Generation Z’s buying behavior of livestock products. Asian J Agric 9: 898-905. This study aims to analyze the effect of social media marketing on the purchasing decisions of Generation Z in Makassar City, South Sulawesi, Indonesia. The background of this study lies in the increasing use of social media as a primary source of information, interaction, and product evaluation among Generation Z, particularly in the context of e-commerce for processed broiler-based livestock products. The research was conducted in November 2024 using purposive sampling, targeting respondents aged 18-27 years who actively use social media and have purchased processed livestock products through online platforms. The questionnaire consisted of eight measurement items—four indicators of social media marketing and four indicators of purchase decision—evaluated using a five-point Likert scale. A descriptive and quantitative research approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method and processed with SmartPLS version 4 software. The measurement model demonstrated good reliability and validity, as reflected by Average Variance Extracted (AVE) values above 0.50, Composite Reliability exceeding 0.70, and a Standardized Root Mean Square Residual (SRMR) value within the acceptable threshold. The findings indicate that social media marketing has a positive and significant effect on purchase decisions, supported by the statistical results: an original sample (path coefficient) of 0.651, a t-statistic of 10.712—which exceeds the critical value of 1.96—and a p-value of 0.000. These results suggest that the more effective and engaging social media marketing activities are—such as informative content, consistent brand presentation, interactive communication, and accessible product information—the higher the likelihood that Generation Z consumers will purchase processed livestock products through e-commerce platforms. The study emphasizes the importance of strengthening digital marketing strategies for livestock-based SMEs and agribusiness actors seeking to compete in online food markets.